Hungary : economic policies for sustainable growth - Cottarelli, Carlo...[et al] (IMF WashingtonUS, 1998)
Presents a collection of studies focusing on economic developments in Hungary, particularly during 1995-97, a period of momentous changes for the Hungarian economy.